Missense Mutation of TTC7A Mimicking Tricho-Hepato-Enteric (SD/THE) Syndrome in a Patient with Very-Early Onset Inflammatory Bowel Disease - Farela Neves, J (2018)
Tricho-hepato-enteric syndrome (SD/THE) and Multiple intestinal atresia with combined immune deficiency (MIA-CID) are autosomal recessive disorders that present immunological and gastrointestinal features. There are two different phenotypes of patients with TTC7A mutations: the severe form, caused by null mutations and leading to the classical MIA-CID; and the mild form, caused by missense mutations and leading to predominant features of VEO-IBD, less severe immunological involvement and hair abnormalities. We expand the knowledge about TTC7A deficiency, describing a patient with the mild phenotype of TTC7A deficiency but presenting overlapping features of SD/THE and MIA-CID: intestinal atresia and inflammatory bowel disease evocative of MIA-CID, but also dental abnormalities, huge forehead, liver abnormalities, autoimmune thyroiditis and hypogammaglobulinemia, evocative of SD/THE.